Microporous covalent triazine polymers: efficient Friedel–Crafts synthesis and adsorption/storage of CO2 and CH41. Issue 13 (7th April 2015) - Puthiaraj, Pillaiyar; Cho, Sung-Min; Lee, Yu-Ri; Ahn, Wha-Seung
<x xml:space="preserve">Abstract</x> Microporous covalent triazine polymers were synthesized from inexpensive starting materials and their CO2 and CH4 gas uptakes were investigated.